Types of innovation outsourcing: A systemic perspective - Iryna Kornilova; Iryna Horbas; Alona Poltoratska; Iryna Netreba; Oksana Derkach; Tetiana Ovcharenko (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2023)
This article puts forward an approach to systemic understanding of innovation outsourcing types based on the dialectical combination of the general and the specific in outsourcing practice. The study involved synthesis, systematisation, and development of theoretical and applied approaches to identifying types of innovation outsourcing in order to establish a theoretical and methodological foundation for organisations to create their own unique models of innovation outsourcing. The article suggests a classification of innovation outsourcing based on various characteristics, including the nature of the services provided, type of business processes, scope of management function, level of change, nature and organisational form of collaboration, source of resourcing, subjects involved, degree of cooperation, stage of the innovation process, and location of outsourcing service providers. The study demonstrates the cross-functional and multi-faceted nature of outsourcing and possibilities of various combinations of innovation outsourcing types, which should be considered when developing innovation strategies of organisations. The main purpose of the article is to shape a comprehensive understanding of various issues related to making effective managerial decisions regarding possible optimisation perspectives of innovation activities for economic entities through collaboration with outsourcers, determining the form, nature, terms, scale, depth, and other critical elements of such collaboration, and considering a range of their advantages and limitations.
Keywords: O31; O32; F20; 330; Outsourcing; Innovations; Management; Innovation process; Core competencies; Business process; Outsourcing serviceprovider